Exoskeletons for Elderly Activity of Daily Living Assistance: A Review of Upper Limb Exoskeletons and Assessments - Abdul Jalal, Muhammad Fairuz; Harith, Hazreen Haizi; Wan Hasan, Wan Zuha; Salim, Mazatulfazura S.F.; Lin, Ta-Te (International Journal of Integrated Engineering, 2024)
Population ageing is a major global issue faced by almost all countries and regions. As of 2022, the elderly population aged 65 and above made up approximately 10% of the world’s population, with projections suggesting this will rise to 16%, or 1.5 billion individuals, by 2050. The ageing process causes a significant reduction in muscle strength, flexibility, agility, and endurance in the elderly. The application of assistive wearable technology, specifically exoskeletons, is anticipated to enhance elderly performance in activities of daily living. However, exoskeletons are complex integrated systems that exhibit a tight connection with the user and must fulfil various user-specific design requirements in terms of functional performance and user experience. Previous studies have reported several design requirements and evaluations of exoskeletons used to assist the elderly in performing activities of daily living. This review article aims to present an overview of upper-limb exoskeletons designed for elderly assistance, with a focus on exoskeleton types and assessments specifically focused on elderly participation during the assessment, the task performed, and assessment parameters. Seventeen upper limb exoskeletons were identified from the literature and categorised based on supported body segment and structure. Most of the exoskeletons are either in the embodiment design or prototyping stages, and their evaluations were performed in the laboratory or in a simulated environment. Elderly participation in exoskeleton assessment is rare, and there is currently a lack of standardised assessment for exoskeleton assessment.